Packham’s Triumph Pears (Pyrus communis L.) Post-Harvest Treatment during Cold Storage Based on Chitosan and Rue Essential Oil (2020)
: Pears (Pyrus communis L.) cv. Packham’s Triumph are very traditional for human consumption, but pear is a highly perishable climacteric fruit with a short shelf-life affected by several diseases with a microbial origin. In this study, a protective effect on the quality properties of pears was evidenced after the surface application of chitosan-Ruta graveolens essential oil coatings (CS + RGEO) in four different concentrations (0, 0.5, 1.0 and 1.5 %, v/v) during 21 days of storage under 18 ◦C. After 21 days of treatment, a weight loss reduction of 10% (from 40.2 ± 5.3 to 20.3 ± 3.9) compared to the uncoated pears was evident with CS + RGEO 0.5%. All the fruits’ physical-chemical properties evidenced a protective effect of the coatings. The maturity index increased for all the treatments. However, the pears with CS + RGEO 1.5% were lower (70.21) than the uncoated fruits (98.96). The loss of firmness for the uncoated samples was higher compared to the coated samples. The pears’ most excellent mechanical resistance was obtained with CS + RGEO 0.5% after 21 days of storage, both for compression resistance (7.42 kPa) and force (22.7 N). Microbiological studies demonstrated the protective power of the coatings. Aerobic mesophilic bacteria and molds were significantly reduced (in 3 Log CFU/g compared to control) using 15 µL/mL of RGEO, without affecting consumer perception. The results presented in this study showed that CS + RGEO coatings are promising in the post-harvest treatment of pears.